Pengaruh Flash Sale dan Viral Marketing terhadap Impulse Buying dengan Fear of Missing Out (FOMO) sebagai Variabel Moderasi pada Live Streaming Tiktok Shop di Kalangan Generasi Z - Anis Anavia Putri; Sri Wahyuni Ratnasari (Lembaga Pengembangan Kinerja Dosen, 2026)
This study was conducted to determine the relationship between flash sales and viral marketing on impulse buying behavior and to analyze whether fear of missing out (FOMO) can strengthen the influence of both variables on TikTok Shop live streaming activity among Generation Z. The study used a quantitative approach with an associative approach involving 164 respondents aged 18–27. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Based on the analysis, flash sales were proven to have a positive and significant influence on impulse buying. Similar results were found for viral marketing, indicating a positive and significant influence on impulse buying. Furthermore, fear of missing out (FOMO) acted as a moderating variable, strengthening the relationship between flash sales and viral marketing on impulse buying. These findings suggest that marketing strategies utilizing limited promotions, widespread information dissemination, and consumer psychological stimuli can increase the tendency for impulse buying. Therefore, the results of this study are expected to provide considerations for business actors in developing more effective digital marketing strategies, while encouraging consumers to make wiser purchasing decisions.